2020
DOI: 10.3390/pharmaceutics12010031
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Polymer-Based Probes for Fluorescence Guided Visualization and Potential Surgery of EGFR-Positive Head-and-Neck Tumors

Abstract: This report describes the design, synthesis and evaluation of tumor-targeted polymer probes to visualize epidermal growth factor receptor (EGFR)-positive malignant tumors for successful resection via fluorescence guided endoscopic surgery. Fluorescent polymer probes of various molecular weights enabling passive accumulation in tumors via enhanced permeability and retention were prepared and evaluated, showing an optimal molecular weight of 200,000 g/mol for passive tumor targeting. Moreover, poly(N-(2-hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The proper identification of tumor-specific targets for molecular imaging is key to the success of FGS [16,17]. For HNSCC, epidermal growth factor receptor (EGFR) has been identified as a suitable candidate and various exploratory preclinical and clinical trials have indicated the potential of this concept in aiding surgeons during head and neck tumor removal [18,19]. However, an appropriate study comparing the expression of molecular targets suitable for rapid translation towards the clinic in HNSCC and CSSC for the goal of FGS has not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The proper identification of tumor-specific targets for molecular imaging is key to the success of FGS [16,17]. For HNSCC, epidermal growth factor receptor (EGFR) has been identified as a suitable candidate and various exploratory preclinical and clinical trials have indicated the potential of this concept in aiding surgeons during head and neck tumor removal [18,19]. However, an appropriate study comparing the expression of molecular targets suitable for rapid translation towards the clinic in HNSCC and CSSC for the goal of FGS has not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the targeting efficacy was found significantly higher for the monoclonal antibodies in contrast to smaller molecular weight targeting ligands. Even in the case of multiple presentations of oligopeptides originated from the active site of antibodies, it is not able to reach the same affinity to their target ligands [ 119 ]. Recently, the targeting efficacy of antibody-targeted pHPMA nanomedicines was reviewed in detail [ 120 ].…”
Section: Active Targeting Versus Passive Accumulation Of Phpma Nanmentioning
confidence: 99%
“…Indeed, the efficacy of the active targeting was also thoroughly studied in a time-dependent manner to prove the potential benefit of the active targeting. Either epidermal growth factor (EGF)-based [ 125 ] or tumor endothelium-based targeting [ 119 ] have been employed to study the time dependence of the active targeting. In both cases, it was observed that the active targeting is worth being effective in short times up to the 1 or 4 h, respectively.…”
Section: Active Targeting Versus Passive Accumulation Of Phpma Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…Other synthetic molecules such as N -(2-hydroxypropyl) methacrylamide (HPMA), a hydrophilic polymer can increase circulation time [ 96 ]. This has been shown to be efficacious in peptide-based probes against EGFR, which face similar challenges as nanobodies in clearance [ 97 , 98 , 99 ]. The goal is titration of serum half-life to extend the window of time for probe and tumor binding for improved tumor labeling.…”
Section: Potential Challenges Solutions and Future Directionsmentioning
confidence: 99%